ANALISIS HUKUM ISLAM TERHADAP PENGGUNAAN KARTU KREDIT - Muhammad, Muhammad; Rahmad, Rahmad (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
Credit card as one of the most urgent needs for the middle class and above, is a modern payment system with security from the risk of carrying large amounts of cash which is very efficient. Legal provisions for the use of this product are needed, so that it has sharia restrictions, namely sharia provisions regarding the use of credit cards, for Muslims. This research is a literature study related to theoretical studies and other references related to the values, culture, and norms that develop in the social situation under study. The results show that there are three criteria for the theory used as the basis for the research, namely relevance, recency, and originality. Relevance means that the theory put forward is in accordance with the problem under study. The presence of Islamic credit cards that are presented for ease of transactions should not be a catastrophe for Muslims. The use of credit cards is focused on positive things for the security aspect of avoiding carrying large amounts of cash. Islamic credit cards should not be used for transactions that are not in accordance with sharia. The fiqh scholars have determined that it is not permissible to obtain ujrah (fee) for kafalah services, because when the guarantor pays the insured party's obligation, this resembles qardh (loan) which brings profit to the lender and is prohibited by Shariah. Not encouraging excessive spending by setting a maximum spending ceiling and having the financial ability to repay debts on time.